n → ∞ lim n 3 1 3 + 2 3 + ⋯ + n 3 − 4 n = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
L = n → ∞ lim n 3 1 3 + 2 3 + ⋯ + n 3 − 4 n = n → ∞ lim 4 n 3 n 2 ( n + 1 ) 2 − 4 n = n → ∞ lim 4 n 3 n 2 ( n + 1 ) 2 − n 4 = n → ∞ lim 4 n 3 n 4 + 2 n 3 + n 2 − n 4 = 2 1
You should carry the limit to infinity sign along until the last expression.
Log in to reply
Oh!! I thought that I had taken unfortunately I hadn't. I have amended it .
Thank you !!
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Stolz–Cesàro theorem
L = n → ∞ lim n 3 1 3 + 2 3 + ⋯ + n 3 − 4 n = n → ∞ lim 4 n 3 4 ( 1 3 + 2 3 + ⋯ + n 3 ) − n 4 = n → ∞ lim 4 ( n + 1 ) 3 − 4 n 3 4 ( n + 1 ) 3 − ( n + 1 ) 4 + n 4 = n → ∞ lim 1 2 n 2 + 1 2 n + 4 6 n 2 + 8 n + 3 = 2 1 = 0 . 5